Gestão socioambiental e o terceiro setor: avaliação das ações da Associação dos Catadores de Recicláveis de Cabedelo -PB - Gomes, Anderson Emmanuel dos Santos (2011)
The issue of urban solid waste and its forms of management have been widely discussed topic by the current society that seeks to revise their concepts and choices in favor of a better quality of life. The reality of Paraíba this problem of urban waste, currently, little is differentiated from their states of Brazil. Mismanagement of actions guided by public policies that arise in the spheres of sectors - government, market and civil society- has caused further damage to natural resources such as deplored by human action. In this context arise socio-environmental actions of the Third Sector as ACARE - Association of Collectors of Recyclable in Cabedelo-PB - with the objective to minimize the damage suffered by societies because of appropriate non- destination of trash. The need to implement an efficient socio-environmental management of trash and that meets so integral to the layers involved, of the generation to reprocessing or recycling is the impetus for maintaining of quality of life on the planet.